TRANSFORMATIONAL TRENDS AND INNOVATIVE FACTORS IN THE DEVELOPMENT OF THE WHOLESALE AND RETAIL SECTORS OF THE PHARMACEUTICAL MARKET - E. A. Bykova (Вестник университета)
The article discusses important features of trends in the transformation of the wholesale and retail level of the Russian medicinal market in the context of innovative factors in the development of the pharmaceutical industry in Russia. The paper gives a general assessment of the impact of state regulation of the maximum selling prices for medicines from the list of vital and essential medicines on the profitability of the market. The author presents a simplified institutional scheme of interaction between distributors and other market participants. The study discusses important aspects and tactical steps of the distribution and pharmacy level of the Russian pharmaceutical market. The article gives the ratings of the leading distribution pharmaceutical companies in Russia and analyses the peculiarities of their structural changes under the influence of innovative development factors. The paper gives ratings of leading pharmacy chains and analyses the features of new structural formations – associations. The author proposes the term of “polarization” for wholesale and retail companies.